TINJAUAN YURIDIS MENGENAI PROSES PERIJINAN TENTANG DAMPAK LINGKUNGAN (AMDAL) - Lutfi Rumkel; Muhammad Taib Warhangan; Jaidun Samual (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2020)
The purpose of the implementation of screening is to determine whether a project needs to be done AMDAL or not, the determination of a project will speed up the process of implementing the preparation of AMDAL as a condition for obtaining a permit. The procedure for the establishment of amdal assessment commission in regency/city area is regulated through the Decree of the Minister of Environment No. 41 of 2000 on Guidelines for the Establishment of District/City AMDAL Assessment Commission, while the authority to assess the results of AMDAL in district/city areas is regulated through the Decree of the Minister of Environment No. 40 of 2000 on the Working Code guidelines of the AMDAL Assessment Commission. Based on Article 1 paragraph (2) of the Decree of the Minister of Environment No. 40 of 2000 the position of the AMDAL Appraiser commission is located at the central level of himgga in the district / city. Position of AMDAL Assessment Commission: a) The Central AMDAL Assessment Commission is in the Ministry of Environment; b) Provincial AMDAL Assessment Commission is located in Bapedalda Province; c) The District/City AMDAL Assessment Commission is located in Bapedalda/District/City Environmental Management Section. Then in Article 1 paragraph (6) written the District/City Assessment Commission is authorized to assess the results of the analysis on the environmental impact for all business plans and/or activities outside the authority of the Central and Provincial, as stipulated through the Decree of the Minister of State of the Environment on The Type of Business and/or Activities that must be Supplemented by analysis of environmental impacts. Analysis of Environmental Impact in Government Regulation No. 27 of 1999 on Environmental Impact Analysis mentioned that AMDAL is a study of the large and important impact of decision-making of a business and/or planned activities on the environment necessary for the decision-making process on the implementation of business and/or activities.